Narodni adresar hrvata-slovenaca-srba = The national directory of the croat-slovene-serb organizations, institutions, business, professional and social leaders in the United States and Canada - Mladineo, Ivan (I. Mladineo, 1937)
U oba geografska adresara raspored ustanova, poduzeća i dr. prema državama i mjestima.